COMPARISON OF STRUCTURE AND COMPOSITION OF MANGROVE TYPES IN BONTO BAHARI AND AMPEKALLE AREA, MAROS REGENCY - Rukminasari, Nita; Kadir, Amelia; Kudsiah, Hadiratul; Yunus, Budiman (Hasanuddin University, 2025)
Mangrove ecosystems play a crucial role in coastal protection and biodiversity conservation. However, few studies have compared the structures and compositions of mangrove species across different regions. This study analyzed the structural differences and species composition of mangroves in Bonto Bahari and Ampekalle in Maros Regency. This study employed a line transect and plot method to assess tree density, canopy cover, and vegetation height. The results showed that Ampekalle had the highest canopy cover percentage, indicating a more stable environment for mangrove growth. Rhizophora mucronata was the dominant species across all sites, with the highest tree density recorded at Ampekalle. Differences in vegetation height suggest variations in soil conditions, water availability, and sunlight exposure. These findings emphasize the ecological importance of Ampekalle as a priority area for conservation. Further research is required to explore the environmental factors influencing mangrove distribution.